Discrimination against people with severe mental illness and their access to social capital: findings from the Viewpoint survey. (20th May 2013) - Webber, M.; Corker, E.; Hamilton, S.; Weeks, C.; Pinfold, V.; Rose, D.; Thornicroft, G.; Henderson, C.
Abstract : Aims: Discrimination against people with severe mental illness is an international problem. It is associated with reduced social contact and hinders recovery. This paper aims to evaluate if experienced or anticipated discrimination is associated with social capital, a known correlate of mental health. Methods: Data from the annual viewpoint cross-sectional survey of people with severe mental illness ( n = 1016) were analysed. Exploratory univariate analysis was used to identify correlates of social capital in the sample, which were then evaluated in linear regression models. Additional hypotheses were tested using t tests. Results: Experienced discrimination made a modest contribution to the explained variance of social capital. Experienced discrimination from friends and immediate family was associated with reduced access to social capital from these groups, but this was not found for wider family, neighbours or mental health staff. Experience of discrimination in finding or keeping a job was also associated with reduced access to social capital. Conclusions: Further longitudinal research is needed to determine how resources within people's networks can help to build resilience, which reduces the harmful effect of discrimination on mental health.